1994
DOI: 10.1021/np50112a002
|View full text |Cite
|
Sign up to set email alerts
|

Bistramides A, B, C, D, and K: A New Class of Bioactive Cyclic Polyethers from Lissoclinum bistratum

Abstract: The isolation and characterization is described of four novel cyclic polyethers, bistramides B [2], C [3], D [4], and K [5], which are closely related to the previously reported bistramide A [1] from the New Caledonian urochordata Lissoclinum bistratum. The structures of these metabolites were defined by spectroscopic methods. The four compounds exhibited in vitro cytotoxicity toward six tumor cell lines, including the human non-small cell lung carcinoma (NSCLC-N6) line. Cytofluorimetric analysis with bistrami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 5 publications
1
74
0
Order By: Relevance
“…TB1. The extract of L. bistratum also contained major metabolites, including the bistramides and the bistratamides group of compounds (Degnan et al, 1989;Biard et al, 1994;Perez and Faulkner, 2003). However, in most samples, especially those from California, the majority of the components could not be assigned from databases, such as Antimarin and the Dictionary of Natural Products.…”
Section: Bioactivity Profile Of Ascidian Chemical Extractsmentioning
confidence: 99%
“…TB1. The extract of L. bistratum also contained major metabolites, including the bistramides and the bistratamides group of compounds (Degnan et al, 1989;Biard et al, 1994;Perez and Faulkner, 2003). However, in most samples, especially those from California, the majority of the components could not be assigned from databases, such as Antimarin and the Dictionary of Natural Products.…”
Section: Bioactivity Profile Of Ascidian Chemical Extractsmentioning
confidence: 99%
“…Its ring and tail moieties together are essentially the structural equivalent for half of the dimeric cyclic lactone of swinholide A [46]. (vii) Finally, bistramides are a unique family of dilactam polyethers isolated from the marine ascidian Lissoclinum bistratum that have recently been shown to target actin with high affinity and inhibit filament formation and promote filament disruption [47][48][49]. Interest- ingly, there is virtually no structural similarity between bistramides and other known G-actin-binding toxins.…”
Section: Barbed End-targeting Compoundsmentioning
confidence: 99%
“…In addition, we demonstrated that the C(1)-C(4) enone-containing subunit of this natural product plays a pivotal role in covalent modification of cellular actin, which further enhances the cytotoxicity of the corresponding bistramide-based compounds. Our study provides comprehensive characterization of the unique mode of action of bistramide A and identifies structural requirements of bistramides that are responsible for severing actin filaments and inhibiting growth of cancer cells in vitro and in vivo (18)(19)(20).…”
mentioning
confidence: 99%